Estudos estruturais e funcionais de duas β-glicosidases de Trichoderma harzianum - Mutti, Hêmily Sanches (Universidade Federal de São Carlos, 2014)
The depletion of fossil fuels, the growing energy demand and the great need to reduce carbon emissions gradually increased the demand for new sources of renewable and clean energy. Bioethanol is obtained from the fermentation of lignocellulosic biomass, for example sugar cane, and can be considered a viable alternative. For this biomass can be used it is necessary to degrade the constituent molecules of the cell wall to fermentable sugars through the enzymes called cellulases. Among them there are three classes with different functions: the cellobiohydrolases, endoglucanases and β-glucosidases. In order to contribute to the viability and deployment of ethanol production technologies, purification of two β- glucosidases of the fungus Trichoderma harzianum was performed, named in this work as ThBgl1 e ThBgl2, as well as their biophysical and biochemical characterization. Clones in study were obtained by a cloning platform, expression and purification of recombinant proteins in high performance and expressed in bacteria Escherichia coli. Through the functional characterization of proteins under study it was found that they had the optimum pH in the range of 5.5 and optimum temperature around 40ºC. Results of enzyme kinetics showed that ThBgl1 has higher preference (specificity) by cellobiose, while in ThBgl2 cellobiose is a substrate having low specificity. In ThBgl2 specificity is higher by fucosideos. Furthermore, it was observed the occurrence of transglycosylation catalyzed by β-glucosidases in study and the action of some inhibitors on its enzymatic activity. The three-dimensional analysis of these proteins revealed the presence of the barrel tim typical of family 1 of glycoside hydrolases.
Keywords: Biotecnologia; Trichoderma harzianum; Cinética enzimática; Enzyme kinetics; OUTROS